Mid-Term Evaluation Report on the Enhanced Data Dissemination Initiative Project. (Policy Papers; Policy Paper ;, 2013)
This report presents the results of the mid-term evaluation of the Enhanced Data Dissemination Initiative (EDDI) financed by the United Kingdom's Department for International Development (DFID) covering the period April 1, 2010 to September 30, 2012. The evaluation was conducted internally by the IMF in consultation with DFID. EDDI is a five-year project (April 2010-March 2015) implemented by the IMF to improve macroeconomic statistics in 25 African countries. The project includes modules for sub-groups of countries covering national accounts, monetary statistics, government finance statistics (GFS), balance of payments statistics (BOP), and harmonization of statistics in several regional organizations. The mid-point of a five-year project is an appropriate time for all stakeholders of the project to step back and take stock of what has been accomplished in the first half of the project, what has gone well, what aspects have been disappointing, and what might be adjusted or changed to make the remainder of the project more effective in achieving its objectives. To facilitate this process, questionnaires were developed to obtain feedback from three groups: counterparts in participating countries, IMF module managers and experts, and DFID country and regional advisors. Recommendations made by the stakeholders that will be followed up in the second half of the project are listed as bullets in italics below.